IMMUNOPROTEOMICS APPROACH FOR SYNTHETIC VACCINE DEVELOPMENT FORM STREPTOCOCCUS DYSGALACTIAE SUBSP. EQUISIMILIS - GOMASE V.S.,; CHITLANGE N.R., (International Journal of Pharma and Bio Sciences, 2010)
Streptococcus dysgalactiae subsp. equisimilis are the causative organisms of infections with Betahemolytic group C and G streptococci. Peptide fragments of antigen protein can be used to select nonamers for use in rational vaccine design and to increase the understanding of roles of the immune system in infectious diseases. Analysis shows MHC class II binding peptides of antigen protein from Streptococcus dysgalactiae are important determinant for protection of host form bacterial infection. In this assay, we used PSSM and SVM algorithms for antigen design and predicted the binding affinity of bacterial protein having 200 amino acids, which shows 192 nonamers. Binding ability prediction of antigen peptides to major histocompatibility complex (MHC) class I & II molecules is important in vaccine development from Streptococcus dysgalactiae.